The Effectiveness of Foot Massage Therapy as Additional Complementary Therapy in Post-SC Patients in the ICU Room: A Case Report - Ilzam Suji Ajikumoro; Rismawan Adi Yunanto; Rondhianto Rondhianto; Heri Siswanto (Jurnal Kegawatdaruratan Medis Indonesia, 2026)
Patients with pregnancy complications, especially placenta increta, which results in antepartum hemorrhage, will experience hemodynamic instability. Patients who are at risk of long-term hypovolemia are at risk of hemodynamic instability. Hemodynamic instability, or unstable blood flow, is common in critically ill patients requiring intensive care. One additional non-pharmacological therapy that can support the hemodynamic status of ICU patients is foot massage. The purpose of this study was to test the effectiveness of the Foot Massage Therapy intervention in post-CS patients in the ICU. The research method used was a case study, with a 4-day research period. Data collection began with medical records, assessments, and observations. Based on the evaluation results before and after the foot massage procedure, significant improvements in MAP, blood pressure, RR, and pulse rate were observed, with SPO2 values remaining unchanged. Foot massage therapy is effective for patients with APB in the intensive care unit, with significant changes in hemodynamic status. Therefore, this foot massage technique can be applied in all hospital rooms and is quite effective as a complementary therapy to stabilize patient hemodynamics, especially in the ICU.